Performance Enhancement of Radial Distribution System via Network Reconfiguration: A Case Study of Urban City in Nepal - Pandey, Govinda Prashad; Shrestha, Ashish; Mali, Bijen; Singh, Ajay; Jha, Ajay Kumar (Journal of Renewable Energy, Electrical, and Computer Engineering, 2021)
Increasing unplanned energy demand increase has led to network congestion, increases power losses and poor voltage profile. To decrease these effects of an unmanaged power system, distribution network reconfiguration provides an effective solution. This paper deals with improving the power losses and poor voltage profile of the Phulchowk Distribution and Consumer Services (DCS) via the implementation of an optimum reconfiguration approach. A Genetic Algorithm (GA) is developed for the optimization. Further, it tries to answer to what extent can we improve the distribution system without overhauling the entire network. The developed simulation algorithm is firstly put into work on the IEEE 33 bus system to better its voltage profile and the poor power losses. The effectiveness of the developed system is validated as it reduced the voltage drop by 5.66% and the power loss by 25.96%. With the solution validated, the algorithm is further implemented in the case of Pulchowk DCS. After reconfiguring the system in different individual cases, optimum network reconfiguration is selected that improved the voltage profile by 3.85%, and the active and reactive power losses by 44.29% and 45.54% respectively from the base case scenario.